Minimization of two-phase flow frictional pressure drop in small channel with environmentally friendly refrigerant - Qais Abid Yousif, 1963- author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Ph.D (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2018